Ethics of Educators and Students According to 'Aidh al-Qarni in the Book Iqra' Bismirobbika - Ridho, Muhammad; Arsyad, Junaidi; OK, Azizah Hanum (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study aims to examine the concept of educator and student ethics according to 'Aidh Al-Qarni in the book Iqra’ Bismirobbika and its relevance to modern education. The research is motivated by the decline of moral values in education, where the teacher–student relationship has begun to lose its ethical and spiritual meaning. Al-Qarni’s views, which emphasize sincerity, purity of heart, and compassion in the educational process, form the foundation of this study. The research employs a qualitative approach through library research. The primary source is Iqra’ Bismirobbika (2005) along with other works of Al-Qarni, analyzed using content analysis to explore the ethical values contained within. The results show that educator ethics include sincerity, compassion, gentleness, purity of heart, and honesty, while student ethics involve sincere intention for Allah, respect for teachers, avoidance of sin, and the practice of knowledge. These values remain relevant as moral guidelines for Islamic education in the modern era.